(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The rapid escalation of multi-drug resistant (MDR) bacterial pathogens represents an alarming global public health crisis. Conventional antibiotics are increasingly rendered ineffective due to complex microbial defense pathways, including enzymatic degradation by β-lactamases, alteration of target sites (e.g., DNA gyrase, DHFR), and efflux pump overexpression. Standard drug discovery pipelines are often slow, resource-intensive, and reliant on hazardous chemical solvents and toxic reagents. Objectives: This study aims to design, synthesize, and bio-evaluate novel bio-derived scaffold hybrid molecules to combat MDR microbial strains through an environmentally sustainable, green chemistry framework. Methodology: An integrated four-step sustainable research workflow was employed: (1) In Silico Lead Discovery: Computer-simulated molecular docking was performed against critical MDR bacterial targets (β-lactamase, DNA gyrase, and DHFR) to predict binding affinity, evaluate structural orientation, and optimize lead selection prior to wet-lab synthesis. (2) Microwave-Assisted Green Synthesis: Target scaffold hybrids, combining biologically active natural product frameworks from plant and microbial origins, were synthesized using direct volumetric microwave heating, eliminating harsh organic solvents and drastically reducing reaction times from hours to minutes. (3) Eco-Friendly RP-HPLC Quantitation: Compound purity, yield, and stability were verified using greener Reverse-Phase High-Performance Liquid Chromatography utilizing low-volume, benign mobile phases. (4) Biological Evaluation: Synthesized hybrids were evaluated for target enzyme inhibition and antimicrobial efficacy against MDR strains. Results: Molecular docking identified optimal hybrid candidates demonstrating superior binding energies and tight active-site interactions compared to standard inhibitors. The microwave-assisted synthesis yielded target hybrids with significantly enhanced reaction rates, reduced by-products, and a 90% reduction in energy and solvent waste generation. Green RP-HPLC protocols provided high-resolution analytical quantitation while minimizing hazardous waste. In vitro assays confirmed potent multi-target enzyme inhibition and restored antibiotic susceptibility against resistant strains. Conclusion: Combining computer-aided screening, rapid microwave heating, and eco-friendly chromatographic analysis establishes a high-yield, cost-effective, and environmentally responsible paradigm for next-generation drug discovery against multi-drug resistant pathogens.